Professional guide to signs & symptoms. (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins, 2007)
"This book features: more than 550 signs and symptoms; easy alphabetical organization; history-taking and physical examination guidelines; emergency interventions for life-threatening indicators; cultural cues and gender cues to key ethnic and gender variations in clinical presentation; examination tips to elicit, pinpoint, or characterize a sign or symptom; herb alerts that warn about herbal remedies as causes; appendices of less-common signs and symptoms, adverse reactions to herbs, and effects of biological weapons; and table of English-Spanish translations."--Jacket.
Signs and symptoms -- Selected signs and symptoms -- Potential agents of bioterrorism -- Common signs and symptoms associated with herbs -- Obtaining a health history -- Guide to laboratory test results.
Includes bibliographical references (pages 868-869) and index.
Keywords: SYMPTOMS -- HANDBOOKS, MANUALS, ETC